What is the Nature of Language? How does it Behave? What is Language Learning then? A Review Paper in Applied Linguistics - Job W. Mwakapina (Randwick International of Education and Linguistics Science Journal, 2021)
Language is viewed differently by people from different fields, and one of the reasons why linguists and philosophers encounter difficulties in clarifying what the study of language should involve has to do with the general view that language means many things to people from different disciplines. This paper provides a comprehensive and analytical discussion patterning to the nature of language, theories, methods, and approaches to language teaching and learning based on a literature review. In particular, the paper answers questions of what is the nature of language, what is involved in the study of a language and how does it behave? And how language can be taught effectively? To address these questions, the paper has reviewed various studies on the definition of language and the trend in trying to define language. Also, it has examined how much scholars have defined language economically, but adequately, and it has discussed the nature of language and its assumptions or theories, then it has indicated how language can be best taught. The review indicates that there are conflicting claims about the nature of language, and thus, it is difficult to define the nature of language or to tie it down to one statement, for it means many things to different people. The paper concludes that it is difficult to define the nature of language comprehensively in one statement, and the concept of language teaching is mainly influenced by the idea of the nature of language, and on how language is taught and learnt. Therefore, success in language teaching depends on the learning environment, how a teacher views what is a language or the nature of language and on the motivations of learning provided to the learners.